The Influence of WE-ARe (Warm-Up, Exploring, Argumentation, Resume) Model Integrated with 21st-Century Skills on Prospective Biology Teachers' Communication Skills - Amin, A. M.; Adiansyah, R.; Mustami, M. K.; Yani, A.; Hujjatusnaini, N.; Ahmed, M. A. (Jurnal Pendidikan IPA Indonesia, 2024)
The research aims to identify the influence of the WE-ARe (Warm-up, Exploring, Argumentation, Resume) model integrated with 21st-century skills on prospective biology teachers’ communication skills. The research type was quantitative, using a quasi-experiment research design. The research sample consisted of 60 biology education students in three classes. The research instruments used were valid and reliable observation sheets and questionnaires to measure communication skills. Data were analyzed using Covariate Analysis (ANCOVA) with a significant level of 5%. The research shows that the average communication in the experimental group after receiving treatment is 90.63, while in the positive control group, it is 73.54, and in the negative control group, it is 39.14. The test results to find out the difference in communication skills between the experimental and control groups obtained a calculated F value of 2846.491 with a significance value of 0.000. The significance value is smaller than the real level alpha 5% or (0.05). The research concludes that there is an influence of the WE-ARe model integrated with 21st-century skills on prospective biology teachers’ communication skills. The learning phases of the WE-ARe model integrated with 21st-century skills are proven to improve verbal and non-verbal communication skills. WE-ARe is a new learning model developed by researchers to accommodate the learning needs of students in the Industry 4.0 era towards the Society 5.0 era by using the principles of constructivism, collaborative, and participatory elaboration. The research is expected to contribute to increasing the global competence of university graduates, especially teachers.